Penguatan Nilai Al Islam dan Kemuhammadiyahan guru TK ‘Aisyiyah Kota Mataram Melalui Baitul Arqom - Mardiyah Hayati; Niswatun Hasanah; Yuliananingsih Yuliananingsih (El-Khidmat, 2024)
The aim of this study is to evaluate and measure the impact of implementing the Baitul Arqom program on the understanding, application, and internalization of the values of Al-Islam and Kemuhammadiyahan among teachers of TK ‘Aisyiyah Bustanul Athfal in Mataram City. The program utilized andragogical methods to strengthen these values, involving 49 teachers from the Ikatan Guru Bustanul Athfal (IGABA) Kota Mataram, guided by Master of Training, Mardiyah Hayati, M.Pd.I, and three other competent instructors. The implementation comprised preparation of materials and instructors, opening and introduction, instructional sessions by the instructors, group discussions, case studies and role plays, and reflection sessions. Evaluation was conducted through questionnaires and interviews, and each participant was required to develop a follow-up plan to implement the learned values in their respective schools. Results indicated a significant improvement in understanding the values of Al-Islam and Kemuhammadiyahan, enhanced applicative skills in teaching, as well as increased commitment and integrity among participants. The positive impact of the program was evident in participants' ability to design and implement Islamic values-based learning activities, and their commitment to internalize these values in their daily tasks. However, challenges remain in ensuring the long-term implementation of these values, requiring continuous support and monitoring from IGABA and MPK PDA Kota Mataram. The success of the Baitul Arqom program in Mataram City demonstrates its potential for adaptation and implementation in other regions with adjustments to local needs. The program not only improved the quality of education in TK 'Aisyiyah Bustanul Athfal schools but also strengthened teachers' commitment to educating the younger generation with strong Islamic values. Overall, the program successfully achieved its goals and made a significant contribution to enhancing the quality of Islamic education in Mataram City.